Hubungan Otonomi Daerah dan Kesejahteraan Orang Indonesia - Fajri, Muhammad Azka Nurul (Jurnal Ilmiah Administrasi Publik, 2021)
In approximately two decades of the implementation of the policies of regional autonomy in Indonesia, there are still debates on whether well-being for Indonesian people is created. The debates revolve around the theoretical and empirical gaps between the field and actual policy implementation. This research examines the relationship between regional autonomy and the Indonesian people well-being. A multilevel analysis method was used to test whether regional autonomy significantly relates to the Indonesian people well-being. The statistical data on regional autonomy were obtained from related Ministries and Institutions. Furthermore, the data on well-being were sourced from the 2017 Happiness Level Measurement Survey (SPTK) in the Central Statistics Agency. The results show that regional autonomy is not significantly related to the Indonesian people well-being.